Optimization of the investment portfolio structure of private pension funds in crisis - Небаба, Наталія Олександрівна (Technology audit and production reserves, 2015)
Investing pension assets is one of the most important activities of private pension funds. The amount of funds to individual account of future retiree and pension that he will receive in the future are depended from profitability of assets. After analyzing the existing theory of portfolio investment was concluded impossible to use it without adjustments in the practice of investing pension funds. Thus, there is a need to find approaches to optimize the structure of the investment portfolio of private pension funds, which not only take into account all legislative restrictions on areas for investment and diversification, but also will ensure profitability at an acceptable level. Allowed areas of investing pension funds were investigated in the article and made their retrospective analysis. Using linear programming optimization model that allowed to take into account all the constraints and characteristics of investment assets, it is improved the structure of the investment portfolio of private pension funds. Transferring the results for 2014, it was shown that the use of this model in the non-state pension funds will increase the return on investment that shows the effectiveness of this model.